2018
DOI: 10.1186/s12884-018-1875-1
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of different risk factors and fasting plasma glucose for identifying GDM when using IADPSG criteria: a cross-sectional study

Abstract: BackgroundThe Swedish National Board of Health and Welfare (SNBHW) recommended the new diagnostic criteria for GDM based upon Hyperglycaemia and Adverse Pregnancy Outcomes (HAPO) study thresholds. Due to limited knowledge base, no recommendations were made on GDM screening. The aim of this study is to evaluate test characteristics of risk factors and fasting blood glucose as screening tests for diagnosing GDM using diagnostic thresholds based upon HAPO study 1.75/2.0 (model I/II respectively) odds ratio for ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 33 publications
2
12
2
1
Order By: Relevance
“…Although both studies were performed in pregnant individuals, Agbozo et al 25 screened subjects using a universal approach when compared to the selective screening based on risk factors that was used in this study. This could have accounted for the higher specificity found in this study; however, the finding was higher than the positive-predictive value found in a study by Saeedi et al, 26 which gave positive-predictive value of 78% at FPG threshold of 5.2 mmol/L. However, Saeedi et al 26 screened a population of pregnant females with known risk factors for gestational diabetes and the study was carried out in Swedish population.…”
Section: Roc Curve 1 -Specificitycontrasting
confidence: 70%
See 1 more Smart Citation
“…Although both studies were performed in pregnant individuals, Agbozo et al 25 screened subjects using a universal approach when compared to the selective screening based on risk factors that was used in this study. This could have accounted for the higher specificity found in this study; however, the finding was higher than the positive-predictive value found in a study by Saeedi et al, 26 which gave positive-predictive value of 78% at FPG threshold of 5.2 mmol/L. However, Saeedi et al 26 screened a population of pregnant females with known risk factors for gestational diabetes and the study was carried out in Swedish population.…”
Section: Roc Curve 1 -Specificitycontrasting
confidence: 70%
“…This could have accounted for the higher specificity found in this study; however, the finding was higher than the positive-predictive value found in a study by Saeedi et al, 26 which gave positive-predictive value of 78% at FPG threshold of 5.2 mmol/L. However, Saeedi et al 26 screened a population of pregnant females with known risk factors for gestational diabetes and the study was carried out in Swedish population. Geographical variation in risk factors may be possible explanations for these differences observed.…”
Section: Roc Curve 1 -Specificitycontrasting
confidence: 70%
“…40,41 Many studies considered the increasing level and cutoff points of FBS in early pregnancy as a risk factor for GDM, but their results are inconsistent. [42][43][44] The areas and ethnic variations among participants, and the different diagnostic criteria for GDM may explain the reasons for these inconsistencies. In this study, the association between the elevated level of FBG in the first trimester and GDM might be relevant to the high-carbohydrate diet of women in the northwest of China.…”
mentioning
confidence: 99%
“…90 Likewise, a retrospective study found that risk factor screening for GDM alone or in combination with random capillary glucose was poorly predictive of GDM, but FPG 4.8-5.0 mmol/l showed good test characteristics and resulted in a low rate of OGTTs needed. 91 A study evaluating FPG as a screening tool to rule-out GDM in a lowrisk population found that women with FPG ≤3.4 mmol/L were at low risk of developing GDM with a sensitivity of 91.3%, thereby avoiding a two-step screening in 10% of their population. 92 Some authors suggest that sensitivity and specificity for risk-factor based GDM screening could be considerably improved by using clinical risk prediction models that include combinations of several risk indicators in combination with FPG for improved prediction.…”
Section: Additional Screening Methodsmentioning
confidence: 99%
“… 90 Likewise, a retrospective study found that risk factor screening for GDM alone or in combination with random capillary glucose was poorly predictive of GDM, but FPG 4.8–5.0 mmol/l showed good test characteristics and resulted in a low rate of OGTTs needed. 91 A study evaluating FPG as a screening tool to rule-out GDM in a low-risk population found that women with FPG ≤3.4 mmol/L were at low risk of developing GDM with a sensitivity of 91.3%, thereby avoiding a two-step screening in 10% of their population. 92 …”
Section: Overview Of the Included Publicationsmentioning
confidence: 99%